Kinerja Guru PAUD Dilihat dari Motivasi dan Lingkungan Kerja - Yusuf Iskandar (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2022)
This study aims to determine the effect of work motivation and work environment on teacher performance in early childhood education in Sumberpucung District, Malang, both partially and simultaneously. The research method used was a quantitative method through an associative approach. The sample selection method in this study was a saturated sample (census) of 50 teachers. Data analysis techniques using the classic assumption test, multiple linear regression test, F test and t test. The results of this study indicate that: 1) Work motivation and work environment simultaneously influence teacher performance. 2) Partially, work motivation has a positive and significant effect on teacher performance. 3) The work environment has a positive and significant effect on teacher performance